Différent-e - Eau’Rageuses; Eli (Glad!)
I’ve drawn lines, handsome lines, straight and harmonious, meaningful and concrete lines. I’ve shaped and modeled my being. The more readable I became, the less I could read myself. Within me has grown disgust. I wrote this text to remind me that I was, that I am, that I will be, because it is not easy every day, when we swing between the lines, to be sure that we’re there.